The Skinhead Subculture in the Czech Republic - Smolík, Josef (Kultura-Społeczeństwo-Edukacja, 2015)
This article briefly describes the skinhead subculture, its history, components, characteristics, values, attitudes and norms. It also presents the various currents of the subculture, with an emphasis on the current apolitical trend within this subculture. The article discusses not only the skinhead subculture in England (its roots, development, etc.), but also the situation in the Czech Republic. The skinhead scene in the Czech Republic is characterised by disunity, caused by political orientation and the engagements of its various supporters, who identify either with: (a) the extreme right (National Socialism), (b) the traditional current (patriotism and the classic themes of the original skinhead subculture), or (c) the extreme left (Trotskyism, communism, and anarchist or ‘autonomist’ currents). It is difficult to establish how many skinheads there are in the Czech Republic today, but one estimate puts the figure at five thousand people when adding all currents together.